Rethinking the pornography debate in Greece: A country-specific reading of an 'old' argument - Tsaliki, Liza; Chronaki, Despina (My University, 2015)
Given the widely circulated anxieties about the consumption of pornography and its presumed effects on adults and youngsters, as well as the intensification of moral, social and feminist campaigns to counter its spread, especially through online technologies, this article wishes to offer a country-specific contextualization of the pornography debate in Greece. Taking into account the pro-effects reading of the culture of pornography that permeates the Greek context, and a media agenda that mainly concentrates public discussion on children who are 'at risk' from the consumption of porn, we wish to argue that it is the legacy of the Greek erotic cinema of the mid-seventies and the particular way the feminist movement developed in the country which account for the public debate on pornography in Greece.
Keywords: Risk-factors; Internet; Exploration; Exposure; Culture; Online; Sex